Prenatal health behaviours as predictors of human placental lactogen levels - Garay, Samantha M.; Sumption, Lorna A.; John, Rosalind M. (Frontiers in Endocrinology, 2022)
Introduction Placental lactogen (hPL) is a key hormone of pregnancy responsible for inducing maternal adaptations critical for a successful pregnancy. Low levels of placental lactogen have been associated with lower birth weight as well as symptoms of maternal depression and anxiety. Lower placental lactogen has been reported in women with higher body mass index (BMI) but it is unclear whether prenatal health behaviours predict hPL levels or if hPL is associated with infant weight outcomes. Method This study utilised data from the longitudinal Grown in Wales cohort, based in South Wales. Participants were recruited at the pre-surgical appointment for an elective caesarean section. This study incorporates data from recruitment, post-delivery and a 12 month follow-up. Measures of maternal serum hPL were available for 248 participants. Analysis included unadjusted and adjusted linear and binary regression. Results Unadjusted, prenatal smoking and a Health Conscious dietary pattern were associated with hPL levels, however this was lost on adjustment for BMI at booking, Welsh Index of Multiple Deprivation (WIMD) score and placental weight. When stratified by maternal BMI at booking, a Health Conscious dietary pattern remained associated with increased hPL levels in women with a healthy BMI (p=.024, B=.59. 95% CI=..08,1.11) following adjustment for WIMD score and placental weight. When adjusted for a wide range of confounders, maternal hPL was also associated with increased custom birthweight centiles (CBWC) (p=.014, B=1.64. 95% CI=.33,2.94) and increased odds of large for gestational age deliveries (p=<.001, Exp(B)=1.42. 95% CI=1.17,1.72). Conclusion This study identified that consuming a Health Conscious dietary pattern in pregnancy was associated with increased hPL, within women of a healthy BMI. Moreover, higher hPL levels were associated with increased CBWC and increased odds of delivering a large for gestational age infant. This improves the current limited evidence surrounding the nature of hPL in these areas.